Analyse de l’activité de travail dans la gestion des situations d’urgence - Christine Owen (Activités)
The paper addresses the call by Rasmussen and Svedung (2000) for (i) more research into emergency incident management and (ii) more attention to be given to the nature of emergency-as-activity, rather than the current preoccupation on organisational structures. Drawing on French-speaking and Nordic approaches to activity, this paper proposes a taxonomy of work activity focussed on emergency-as-activity. The taxonomy draws on concepts found in ergonomic research into other HRO domains and empirical analysis conducted in a related HRO environment (air traffic control). The paper constructs a set of propositions that will be empirically tested in a study investigating work activity in multi-agency emergency incident management for bushfires in Australia. The taxonomy based on related HRO environments emphasising communicative practices, proposes that the most salient features of work activity in managing incidents will be their spatio-temporal features, their complexity and the need to act interdependently with others.